Uma nova tecnologia no pensamento de Herbert Marcuse: arte e técnica na sociedade unidimensional - Bezerra, Cícero Leílton Leite (2010)
This dissertation addresses the issue of technology in the work of Herbert Marcuse, explaning the merger between technology and domination that result in a totalitarian technological apparatus. Thus, technological civilization is supported and justified by a rational technological apparatus in the society, we have come not only the philosophy of Marcuse, but other great thinkers too, like Heidegger, Hegel, Marx. We also present a debate involving the philosophy of science, logic and linguage. Marcuse points to the need for a new technological rationality that emerge from a new sensibility, where the technique would allow a new relationship between man and nature. From then on, would emerge the need for a new subject. This transition would be possible by means of sensitivity, where art would become the art of live. With the link between art and technique made possible by new sensitivity, the author leaves one of its main contribution: he leaves open the possibility for the subject to choose new targests for technological development